2018
DOI: 10.3389/fphar.2018.00251
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Rich Extract From Clerodendrum volubile Suppresses Cell Migration; Abates Oxidative Stress; and Regulates Cell Cycle Progression in Glioblastoma Multiforme (U87 MG) Cells

Abstract: Glioblastoma multiforme (GBM) is a malignant primary type of brain cancer with high proliferation and metastasis rates due to involvement of the microglial cell. It is resistant against available chemotherapy. Many strategic protocols have been developed but prognosis and patient life has not improved substantially. In this study, the anti-metastatic and antioxidant effect of fatty acids from Clerodendrum volubile leaves were investigated in U87-MG (Human Glioblastoma Multiforme) cell lines. The extracted fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Studies have reported therapeutic failures in patients owing to difficulty in treatment (Puli et al, 2006). Although medicinal plants have reported to arrest the proliferation of GBM (Erukainure et al, 2018), C. sativa extracts showed no cytotoxic effect on the cells (Figure 7). Thus, insinuating that the plant may not be beneficial in the treatment of GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported therapeutic failures in patients owing to difficulty in treatment (Puli et al, 2006). Although medicinal plants have reported to arrest the proliferation of GBM (Erukainure et al, 2018), C. sativa extracts showed no cytotoxic effect on the cells (Figure 7). Thus, insinuating that the plant may not be beneficial in the treatment of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is a malignant primary brain tumor common in young kids ( Erukainure et al, 2018 ). Studies have reported therapeutic failures in patients owing to difficulty in treatment ( Puli et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…34 Previous reports demonstrated that fatty acids extracted from C. volubile leaves could suppress tumor metastasis and invasion in human neuronal glioblastoma cells. 35 and breast cancer cells. 36 Although the mechanism underlying antimigration, anti-invasion and anti-adhesion effects are still unclear, the result demonstrated that C. inerme methanolic leaves extract could suppress cancer metastasis of lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The dichloromethane (DCM) fraction of the leaves have been reported for its cytotoxic effect on human embryonic kidney (HEK293) cells (Erukainure, Narainpersad, et al, 2018 ). The leaves are rich in phenolics contents which has been correlated with its reported biological activities (Erukainure, Narainpersad, et al, 2018 ; Oboh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 91%
“…Regarded as magic leaves, C. volubile is used in folk medicine for treating ulcers, arthritis, rheumatism, dropsy, and diabetes (Burkill, 1985 ). Its antioxidant activities have been reported in diabetic rats, and cancerous cells which correlates with their antidiabetic and anticancer activities (Erukainure, Ashraf, et al, 2018; Erukainure, Hafizur, et al, 2017 ; 2018 ). The flowers as well as protocatechuic acid and pectolinarigenin isolated from the leaves have been reported for their ability to modulate phagocytic oxidative burst in isolated neutrophils and macrophages which demonstrates their immunomodulatory activities (Erukainure, Hafizur, et al, 2017 ; Erukainure, Mesaik, et al, 2017 ; Erukainure et al, 2016 ).…”
Section: Introductionmentioning
confidence: 98%